Association between prostate-specific antigen density and prostate cancer prediction among Nigerian men - Abudu EK; Okuku CN; Akaiso OE; Fabian UA; Udoh EA; Ukpong AE; Kudamnya IJ; Ajayi OO; Uduma FU; Abudu OO; Ekpo BO (Ibom Medical Journal)
Background: Prostate - specific antigen density (PSAD) has been shown as a valuable diagnostic and predictive tool for prostate cancer.